The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/catal12010022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Property Characterization and Photocatalytic Activity of the Ag3PO4/Gd2BiTaO7 Heterojunction Catalyst under Visible Light Irradiation

Abstract: A new type of Gd2BiTaO7 nanocatalyst (GBT) was synthesized by a high-temperature solid-phase method, and a heterojunction photocatalyst, which was composed of GBT and silver phosphate (AP), was prepared by the facile in-situ precipitation method for the first time. The photocatalytic property of GBT or the Ag3PO4/Gd2BiTaO7 heterojunction photocatalyst (AGHP) was reported. The structural properties of GBT and AGHP were characterized by an X-ray diffractometer, scanning electron microscope–X-ray energy dispersiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…Figure14aillustrates the impact of different pH values on the removal efficiency of CPS using DBHP as the catalyst under visible light conditions and in darkness[110]. Remarkably, DBHP exhibited exceptional and consistent degradation efficiency towards CPS under visible light exposure for pH values of 3, 7, and 11.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…Figure14aillustrates the impact of different pH values on the removal efficiency of CPS using DBHP as the catalyst under visible light conditions and in darkness[110]. Remarkably, DBHP exhibited exceptional and consistent degradation efficiency towards CPS under visible light exposure for pH values of 3, 7, and 11.…”
mentioning
confidence: 88%
“…These results not only underscore the pivotal role of DBHP in enhancing the rate of CPS PDP but also contribute significantly to the broader field of photocatalysis, making them of considerable importance. 14a illustrates the impact of different pH values on the removal efficiency of CPS using DBHP as the catalyst under visible light conditions and in darkness [110]. Remarkably, DBHP exhibited exceptional and consistent degradation efficiency towards CPS under visible light exposure for pH values of 3, 7, and 11.…”
Section: Comparison Of Photocatalytic Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The results of Rietveld refinement for Eu 2 SmSbO 7 showed that the observed intensities and calculated intensities of the pyrochlore-type structure were in fine agreement. Eu 2 SmSbO 7 was a single-phase, cubic crystal system with a space group of Fd3m (modeled to include O atoms) [62]. The atomic structure of Eu 2 SmSbO 7 is shown in Figure 2b, where the cell parameter a for Eu 2 SmSbO 7 is 10.5547 Å.…”
Section: Xrd Analysismentioning
confidence: 99%